Investigating the application of a honeycomb abradable lining in the turbine stage of an aero-engine. (September 2018) - Zhang, Boxiu; Marshall, Matthew
Abstract: Modern aero-engines use abradable linings to reduce axial gas leakage. In this study the wear performance of a new developed nickel superalloy honeycomb abradable lining was investigated on a novel high-speed test rig, using in-situ measurement techniques, combined with post-test microscopy and X-ray fluorescence based elemental analysis. In particular the effect of changing the nickel-aluminide filler ratio was considered, as well as the impact of thermal ageing of the specimens. Compaction of abradable occurs, resulting in fin wear, along with high forces and temperatures. This wear mechanism is cyclic with debris ejection and sparks. Ageing of the abradable generally leads to an increase in fin wear, with the exception that in one case this lead to improved fracture of the abradable and an improved cutting performance by the fin. Highlights: The wear groove surface fractures resulting in releasing of sparks on a cyclic basis. Different Ni-Al content affects the fracture behaviour of the abradable. The fin is less worn when the abradable is easy to fracture. The ageing process changes the wear mechanisms compared to un-aged tests.